A retrospective chart review of subdermal neck coagulation using helium plasma technology. Issue 4 (5th October 2020) - Doolabh, Vaishali; Ruff, Paul
Abstract: Background: A helium‐based plasma technology has recently been cleared by the Food and Drug Administration for cutting, coagulation, and ablation of soft tissue (Renuvion® System; Apyx™ Medical Corporation). As the safety of helium plasma for treating lax and sagging skin in the neck area has not been previously reported, the objectives of this study were to obtain safety results from helium plasma used for neck rejuvenation, to summarize subject and procedure variables, and to assess treatment outcomes for the development of future treatment protocols. Methods: Two retrospective chart reviews were performed using data from patients who had undergone a helium plasma procedure in the neck area to assess safety (Study 1) and effect (Study 2). For Study 2, pre‐ and posttreatment images of treatment areas were assessed by blinded reviewers. Results: In Study 1 ( N = 15), two adverse events felt to be treatment‐related were noted. In Study 2 ( N = 13), mean improvements included a 37.29% reduction in submental angle and reduction in the submental area. Conclusions: Helium plasma technology appears to be a safe and well‐tolerated treatment. Consistent and reproducible tissue contraction in the submental and neck area was observed between the authors' sites.